The lifespan and kinetics of human dendritic cell subsets and their precursors in health and inflammation - Lubin,R; Patel,AA; Mackerodt,J; Zhang,Y; Gvili,R; Mulder,K; Dutertre,C-A; Jalali,P; Glanville,JRW; Hazan,I; Sridharan,N; Rivkin,G; et al. (Journal of Experimental Medicine, 2024)
Dendritic cells (DC) are specialized mononuclear phagocytes that link innate and adaptive immunity. They comprise two principal subsets: plasmacytoid DC (pDC) and conventional DC (cDC). Understanding the generation, differentiation, and migration of cDC is critical for immune homeostasis. Through human in vivo deuterium-glucose labeling, we observed the rapid appearance of AXL+ Siglec6+ DC (ASDC) in the bloodstream. ASDC circulate for ∼2.16 days, while cDC1 and DC2 circulate for ∼1.32 and ∼2.20 days, respectively, upon release from the bone marrow. Interestingly, DC3, a cDC subset that shares several similarities with monocytes, exhibits a labeling profile closely resembling that of DC2. In a human in vivo model of cutaneous inflammation, ASDC were recruited to the inflammatory site, displaying a distinctive effector signature. Taken together, these results quantify the ephemeral circulating lifespan of human cDC and propose functions of cDC and their precursors that are rapidly recruited to sites of inflammation.